The Bones Of The Story : a novel - Goodman, Carol (New York, NY : William Morrow, 2023)
"The twisty locked-room mystery from two-time Mary Higgins Clark Award-winning author Carol Goodman, about a group of former classmates trapped on their college campus-with a murderer among them"--.
new book 2023 summer.
Keywords: College students; Investigations; College teachers; Death; Murder; Revenge; Missing persons